The Implementation of Religious Education to Support the Socialization of Islamic Sharia at Sabang City - Rosnaini (International Journal Education and Computer Studies (IJECS), 2023)
The implementation of Islamic Sharia, particularly in the Aceh region, is considered obligatory. The community bears a moral responsibility to support the socialization of Islamic Sharia. This responsibility falls upon various stakeholders, including teachers, parents, and members of the community. Among these stakeholders, teachers are crucial in imparting religious education both at schools and within the home environment, while the broader community plays a significant role. This thesis explores the execution of religious education in supporting the socialization of Islamic Sharia, with the aim of understanding how Islamic religious education is implemented to foster the acceptance of Sharia principles in the city of Sabang. Additionally, the study seeks to identify the factors influencing the implementation of Islamic Sharia. The research methodology employs a descriptive research method, incorporating both literature review and field research techniques such as observation, interviews, and questionnaires. The study involves a sample of 50 students from MTsN Sabang, school principals, religious studies teachers in both public and religious schools, and a segment of the local community, particularly parents in the city of Sabang. The findings indicate that the implementation of religious education to support the socialization of Islamic Sharia in Sabang is carried out through instructing students on Islamic teachings, encompassing creed, worship, and ethics. Emphasis is placed on guidance regarding the obligation to observe modest dress, perform the five daily prayers, and attend Friday prayers. These teachings are conducted through discussions during Islamic studies in schools. Various factors influencing the implementation of Islamic Sharia include all components of society—teachers, parents, and the surrounding community—especially local leaders. Challenges persist, such as adherence to local customs, insufficient understanding of Islamic Sharia, and disparities in understanding among scholars and religious authorities. Efforts to enhance religious education for the socialization of Islamic Sharia in Sabang include increased teaching hours dedicated to religious studies. This allows for more in-depth exploration and discussions on Islamic Sharia. Recommendations are directed towards teachers to improve their instruction on Islamic teachings and to school principals to allocate specific time for students to discuss Sharia principles. Parents are urged to continuously remind their children to adhere to the implementation of Islamic Sharia.